Perinatal complications and neonatal outcomes in in vitro fertilization/intracytoplasmic sperm injection: a propensity score matching cohort study - Chen, Ying; Zhang, Mengjie; Gao, Yumei; Li, Mingming; Zheng, Wenjun; Guo, Xueyan; Li, Fei (Frontiers in Endocrinology, 2024)
Background: The utilization of in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) has witnessed a significant increase in recent years. However, the comparative perinatal and neonatal outcomes compared to natural pregnancies are unclear. This study aims to compare the outcomes of pregnancies from IVF and ICSI with natural pregnancies. Methods: This retrospective, propensity score-matched cohort study was conducted at the First People's Hospital of Shangqiu and The First Affiliated Hospital of Xinjiang Medical University, involving 5,628 patients from February 2019 to December 2022. It compared pregnancies achieved through IVF/ICSI with those conceived naturally. The primary outcomes assessed were perinatal complications and neonatal health parameters. Propensity score matching and multivariate logistic regression analysis were employed to adjust for potential confounders and identify independent associations. Results: After propensity score matching, the IVF/ICSI group demonstrated significantly higher rates of placental adherence (12.1% vs. 7.4%, p < 0.001) and postpartum hemorrhage (11.1% vs. 7.6%, p = 0.002) compared to the NP group. Neonates in the IVF/ICSI group had a lower gestational age (38.21 ± 2.12 weeks vs. 38.63 ± 2.29 weeks, p < 0.001), reduced birth weight (3159.42 ± 722.75 g vs. 3211.31 ± 624.42 g, p = 0.032), and an increased preterm delivery rate (11.2% vs. 8.9%, p = 0.017). Multivariate analysis further confirmed these findings, highlighting the independent associations between IVF/ICSI and these adverse outcomes. Conclusion: This study suggests a potential correlation between the use of IVF/ICSI and unfavorable perinatal and neonatal outcomes. These findings underscore the critical need for ongoing monitoring and research efforts to enhance the safety and effectiveness of these reproductive technologies.